(untitled) (KMC Journal, 2024)
Sexual harassment (SH) poses a significant threat to mental health, causing profound emotional distress, particularly among women. Despite legal frameworks, the psychological consequences of SH are inadequately addressed. This study examines the prevalence, manifestations and effects of SH through a structured literature review, using sources such as Google Scholar, PsycINFO and PubMed for articles published after 2018 on the psychological effects of SH. The review process included initial screening based on relevance and quality, methodological evaluation and narrative synthesis. The findings reveal SH’s severe psychological impact across various settings, including workplaces, educational institutions and intimate relationships, with consequences like fear, anxiety, shame, depression and confidence erosion. Reluctance to report SH further exacerbates the psychological toll. The study highlights the need for comprehensive strategies, recommending accessible mental health services, educational campaigns and stronger policies. Fostering a culture of respect, equality and inclusion can enhance survivors’ well-being and create a supportive environment.